2008
DOI: 10.1002/ange.200801530
|View full text |Cite
|
Sign up to set email alerts
|

Intense Near‐IR Emission from Nanoscale Lanthanoid Fluoride Clusters

Abstract: Fluoride clusters of lanthanoids can be prepared in organic solvents by metathetical reactions of Ln(SePh)3 with NH4F. The first products of these reactions, [(py)24Ln28F68(SePh)16] (Ln=Pr, Nd; py=pyridine; see structure), are currently the largest discrete lanthanoid clusters ever isolated. Emission experiments on the neodymium compound reveal a near‐IR quantum efficiency of 41 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…[65] Three years later, Hendrickson et al reported on the isolation of an unexpected tetranuclear terbium compound with pyridinoacetate as supporting ligand. [66] Through the use of a modified diketonate with redox-active ferrocenyl substituents on the backbone of the ligand, tetranuclear hydroxo clusters [Ln 4 -(μ 4 -OH) 4 (FcacacPh) 8 ] (with Ln = Yb, Lu; FcacacPh = benzoylferrocenoylmethanide) were obtained in our group (Figure 3). [33] These compounds each feature eight ferrocenyl groups an-chored onto the cubane-like [Ln 4 (μ 4 -OH) 4 ] 8+ unit through bridging/chelating diketonate ligands.…”
Section: The Structure Of the Cluster Core -Fusion Of Rare-earth Metamentioning
confidence: 99%
See 3 more Smart Citations
“…[65] Three years later, Hendrickson et al reported on the isolation of an unexpected tetranuclear terbium compound with pyridinoacetate as supporting ligand. [66] Through the use of a modified diketonate with redox-active ferrocenyl substituents on the backbone of the ligand, tetranuclear hydroxo clusters [Ln 4 -(μ 4 -OH) 4 (FcacacPh) 8 ] (with Ln = Yb, Lu; FcacacPh = benzoylferrocenoylmethanide) were obtained in our group (Figure 3). [33] These compounds each feature eight ferrocenyl groups an-chored onto the cubane-like [Ln 4 (μ 4 -OH) 4 ] 8+ unit through bridging/chelating diketonate ligands.…”
Section: The Structure Of the Cluster Core -Fusion Of Rare-earth Metamentioning
confidence: 99%
“…[3,33] Figure 3. Solid-state structure of [Ln 4 (μ 4 -OH) 4 (FcacacPh) 8 ]. Hydrogen atoms are omitted for clarity.…”
Section: The Structure Of the Cluster Core -Fusion Of Rare-earth Metamentioning
confidence: 99%
See 2 more Smart Citations
“…The design and construction of high-nuclearity lanthanide (Ln) clusters is one of the most active research frontiers in coordination chemistry, not only due to their aesthetically pleasing structures [1] but also their potential applications including luminescence [2], magnetism [3], catalyst [4] and so on [5]. In recent years, chemists have paid much more attention on constructing polymetallic complexes by using calixarenes [6].…”
mentioning
confidence: 99%